Computational Biomechanics for Medicine Deformation and Flow - Nielsen, Poul M.F.; Wittek, Adam.; Miller, Karol; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
One of the greatest challenges for mechanical engineers is to extend the success of computational mechanics to fields outside traditional engineering, in particular to biology, biomedical sciences, and medicine. This book is an opportunity for computational biomechanics specialists to present and exchange opinions on the opportunities of applying their techniques to computer-integrated medicine. Computational Biomechanics for Medicine: Deformation and Flow collects the papers from the Sixth Computational Biomechanics for Medicine Workshop held in Toronto in conjunction with the Medical Image Computing and Computer Assisted Intervention conference. The topics covered include: medical image analysis, image-guided surgery, surgical simulation, surgical intervention planning, disease prognosis and diagnostics, injury mechanism analysis, implant and prostheses design, and medical robotics.
From the Contents: Automatic quantification of congruity from knee MRI -- Computational fluid dynamics framework for large-scale simulation in pediatric cardiology -- Effects of levator ani muscle morphology on the mechanics of vaginal childbirth.
Keywords: Biomedical engineering; Biomaterials; Surgery; Applied mathematics; Engineering mathematics; Mechanics; Mechanics, Applied; Robotics; Automation; Biomedical Engineering and Bioengineering; Biomaterials; Surgery; Mathematical and Computational Engineering; Solid Mechanics; Robotics and Automation